2015
DOI: 10.1111/inm.12135
|View full text |Cite
|
Sign up to set email alerts
|

Family carers' experience of caring for an older parent with severe and persistent mental illness

Abstract: While the burden of caring for older people with chronic medical illness and dementia has been well documented, considerably less is known about how carers develop the strength and resilience to sustain this important role with older family members with mental illness. The aim of the study was to understand the lived experience of primary caregivers of older people with severe and persistent mental illness, and to explore what, if anything, helps to sustain them in their caring role. An interpretative phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 37 publications
4
59
0
2
Order By: Relevance
“…Furthermore, accepting this destiny ameliorated chronic sorrow. Naming and exploring the purpose of imperfections has been shown to provide encouragement, satisfaction, and hope to sufferers . Researchers have suggested that helping sufferers adapt to culture‐focused grieving is preferable for motivating changes in their beliefs .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accepting this destiny ameliorated chronic sorrow. Naming and exploring the purpose of imperfections has been shown to provide encouragement, satisfaction, and hope to sufferers . Researchers have suggested that helping sufferers adapt to culture‐focused grieving is preferable for motivating changes in their beliefs .…”
Section: Discussionmentioning
confidence: 99%
“…Their involvement with services is usually minimal, unplanned and unstructured, and constrained by confidentiality issues and service requirements [31]. AFMs frequently find that supporting a member with PSU has major detrimental effects on their own well-being and their coping resources are often exhausted [5], findings similar to those focusing on families of young people with first-episode psychosis [32] and older adults with mental health disorders [33]. Indeed, England, Kennedy and Horton [34] found that 32% of families report that anger, rage, aggression and violence by the person with PSU causes them the most concern, but often they do not seek external help.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health nurses may be able to educate other nurses and clinicians in this regard, as they often have experience in supporting and helping to sustain carers by providing emotional support and by enhancing carers’ coping strategies (McCann et al . ).…”
Section: Discussionmentioning
confidence: 97%